Therapeutic effect of long‐interval repeated intravenous administration of human umbilical cord blood‐derived mesenchymal stem cells in DBA/1 mice with collagen‐induced arthritis. (21st May 2019) - Yu, Yeonsil; Yoon, Kyung‐Ae; Kang, Tae‐Wook; Jeon, Hyo‐Jin; Sim, Yun‐Beom; Choe, Seung Hoon; Baek, Song Yi; Lee, Seunghee; Seo, Kwang‐Won; Kang, Kyung‐Sun
Abstract: Rheumatoid arthritis (RA) is a common inflammatory chronic disease. It has been reported that mesenchymal stem cells (MSCs) have the effect of immune suppression in collagen‐induced arthritis (CIA) mice model. However, the in vivo therapeutic effect from the long‐interval repeated intravenous administration of human umbilical cord blood‐derived (hUCB)‐MSCs had not been investigated in CIA mice model. This study was undertaken to investigate the effects of long‐interval repeated intravenous administration of hUCB‐MSCs at different doses in CIA mice model. Mice were intravenously injected with three different doses of hUCB‐MSCs once every 2 weeks for three times. RA severity was assessed by clinical joint score and histologic analysis including hematoxylin and eosin staining, safranin‐O staining, and toluidine blue staining. We used real‐time polymerase chain reaction and flow cytometry to quantify differences in inflammatory cytokines and Tregs. Mice treated with hUCB‐MSCs showed significant improvement in clinical joint score. Histologic analysis revealed that hUCB‐MSCs definitely reduced joint inflammation, cartilage damage, and formation of pannus in multimedium and multihigh groups. These hUCB‐MSCs also significantly decreased IL‐1 beta protein levels in multimedium and multihigh groups and IL‐6 protein levels in all hUCB‐MSCs‐treated groups. Furthermore, mRNA levels of IL‐1 beta and IL‐6 were decreased significantly in all hUCB‐MSCs‐treated groups, whereas the expression of anti‐inflammatory cytokine IL‐10 was increased in the multihigh group. Tregs known as suppressor T cells were also significantly increased in the multihigh group. Our findings suggest that long‐interval repeated intravenous administration of hUCB‐MSCs has therapeutic effects by improving symptoms of RA in CIA mice model in a dose‐dependent manner.